2016
DOI: 10.1097/cpt.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Blood Pressure Assessment by Physical Therapists in the Outpatient Setting—An Observational Study

Abstract: Purpose: Although physical therapists (PTs) are equipped and trained with the knowledge of the importance of vital sign assessment and cardiovascular risk factors, there seems to be a discrepancy between the practice guidelines and the actual practice in the clinic. Therefore, the purpose of this study was to observe the frequency with which PTs take and record heart rate (HR) and blood pressure (BP) in the orthopedic outpatient setting during therapy sessions. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…28 In addition, an observational analysis of 74 outpatient sessions, including 15 initial evaluations, noted that HR and BP were taken during only 2 sessions, despite 26% of patients having a history of CVD. 29 Similar findings have been identified in acute care practice where a recent study showed PTs are only taking vital signs 56% of the time in acute care settings. 30…”
Section: Introductionsupporting
confidence: 76%
“…28 In addition, an observational analysis of 74 outpatient sessions, including 15 initial evaluations, noted that HR and BP were taken during only 2 sessions, despite 26% of patients having a history of CVD. 29 Similar findings have been identified in acute care practice where a recent study showed PTs are only taking vital signs 56% of the time in acute care settings. 30…”
Section: Introductionsupporting
confidence: 76%
“…Studies have identified that 75% of home health care patients and 62% of outpatients under the care of physiotherapists were identified as having either pre-hypertensive or hypertensive blood pressure measures [ 21 , 23 ]. Therefore, availability of an automatic blood pressure unit in the home would offer another level of screening in that the older adult could be trained to self-identify factors which may predispose them to a fall (e.g., orthostatic hypotension) as well as hypertensive measures which may warrant further workup by a medical professional.…”
Section: Hop-up-pt As a Case Examplementioning
confidence: 99%
“…However, given the variety of serious health sequalae associated with HTN (e.g., cerebral vascular accident, coronary heart disease, renal disease), a physiotherapist's inclusion of blood pressure (BP) measures in routine care is essential [19,20]. This assertion is further supported by reports that nearly two thirds of adult patients under the care of physiotherapists present with elevated BP readings [21][22][23]. Recommendations for best practices in prevention, detection, evaluation, and management of Fig.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Recent data show that initial heart rates and blood pressures are measured in less than 3% of initial visits in outpatient physical therapy clinics while recommendations state that blood pressure should be measured on all new physical therapy patients. 7,11,15 Severin has recently stated that routine blood pressure screening in outpatient physical therapy practice is an ethical duty of care. 9 This is important because 62% of an outpatient physical therapy population and 68% of a fitness program population have presented for exercise with prehypertension or hypertension.…”
Section: Introductionmentioning
confidence: 99%